Developing a Framework for the Support of Informal Caregivers: Experiences from Sweden, Ireland, and the United States. (March 2023) - Cahill, Suzanne; Bielsten, Therése; Zarit, Steven H.
Policies and services to support informal caregivers vary considerably across countries. This paper examines the role of caregivers and how perspectives on that role may influence the availability of benefits and services in three countries that differ considerably in their care systems - Sweden, Ireland and the United States. We developed a nine-dimensional framework for examining differences, including policies and how the role of caregiver is conceptualized. We found differences in the three countries in how services are organized, which reflected assumptions about the caregiver role. There were also similarities in the three countries. Caregivers held an ambiguous position within each social system and there was little concern for equity in the delivery of support services. Increased clarity about the role of caregivers may facilitate development of policies that more effectively meet their varied needs.